Transition metal complexes with sulfur ligands, 140 - Mononuclear Ni, Pd and Pt complexes with ' S-3 '(2-) thioether thiolate and HNPnPr(3) phosphorane imine ligands [' S-3 '(2-) = bis(2-mercaptophenyl])sulfide (2-)] - Sellmann, Dieter; Geipel, Franz; Heinemann, Frank Wilhelm (European Journal of Inorganic Chemistry, 2000)
Reaction of the trinuclear [M('S-3')](3) complexes M = Ni (4), Pd (5), Pt (6); 'S-3'(2-) = bis (2-mercaptophenyl) sulfide (2-) with HNPnPr(3) yielded the new phosphorane inline complexes [M(NHPnPr(3))('S-3')] M = Ni (1), Pd (2), Pt (3). The complexes 1-3 have been completely characterized and are rare examples of mononuclear phosphorane imine complexes with late transition metals. Spectroscopic and structural results indicate that the HNPnPr(3) ligands favor the ylidic structure when binding to [M('S-3')] fragments. X-ray structure determinations showed that [M(NHPrP3)('S-3')] complexes associate through N-H ... S(thiolate) bridges to give centrosymmetric dimers.
Keywords: phosphorane imine; sulfur ligands; nickel; palladium; platinum